Brief Timelapse on Dendrimer Chemistry: Advances, Limitations, and Expectations. Issue 2 (9th December 2015) - Ornelas, Catia
Abstract : Dendrimers are well‐defined branched macromolecules that have been studied for a wide variety of applications. Possibility to add multiple functionalities in precise locations of the dendritic structure generated great expectations for the application of dendrimers in nanomedicine, however, the number of dendrimer‐based formulations that advance to clinical studies has been somewhat deceiving. This is partially due to the nonreproducible pharmokinetic behavior observed for multifunctional dendrimers synthesized through the random‐statistical approach that leads to mixtures of products. Therefore, it is crucial to develop multifunctional dendrimers with well‐defined structures in order to increase the chances of meeting the clinical expectations placed on dendrimers. This talent article will give an overview of the dendrimer field, discussing the application of dendrimers in nanomedicine, light‐harvesting systems, sensing and catalysis, with a critical analysis on the expectations, limitations, advances, current challenges and future directions. Abstract : Dendrimer timelapse demonstrates constant evolution in dendrimer chemistry enabling their application in nanomedicine, protein mimic, catalysis, light harvesting systems, and sensing. Increasing the variety of functionalities in dendrimers located at precise sites of the dendritic backbone result in versatile multifunctional nanomaterials that in the future might approach the conceptual nanobots.